Finding a needle in the haystack: performing an in-depth literature search to answer a clinical question - George GS (Dove Medical Press, 2014)
Gwen S George, Laurie Anne Ferguson, Patricia F PearceLoyola University New Orleans, School of Nursing, New Orleans, LA, USAAbstract: Evidence-based practice requires clinicians to review current literature for evidence-based information that demonstrates solutions for clinical problems. The daunting process of navigating extensive electronic publication sources, including citation databases, guidelines, and clinical proceedings, can feel much like finding a needle in the proverbial haystack. Knowing where to get information and strategically maneuvering search terms, Boolean operators, and available delimiters requires investment in learning how they work and then skillful deployment. Time spent in learning the systems is gained back by executing a well-honed search that yields citations that are appropriate for the clinical problem. Search terms and use of effective investigative tools focus the search and produce a comprehensive listing of references. The purpose of this article was to detail the steps in completing a comprehensive literature search when focused on a clinical question. Location of pertinent literature, the multiple characteristics of citation databases and instruction on how to use them, as well as how to manage the located citations are included.Keywords: search techniques, evidence-based practice, graduate nursing education